Legal Implementation On Land Border Management Between Indonesia And Papua New Guinea According to Stephen B. Jones Theory - Sudika Mangku, Dewa Gede (Veteran Law Review, 2018)
In the opinion of Stephen B. Jones the management of the border consists of (1) allocation, (2) delimitation, (3) the demarcation of boundaries in the field, and (4) boundary administration. The land border between Indonesia and Papua New Guinea has been arranged inside Memorandum of Understanding In Respect of The Land Boundary on The Island of Irian (New Guinea) and The Territorial Sea and Seabed Boundaries Immediately South of That Islands; Protocol about Report of Conference on Certain Seabed Boundaries Between Indonesia and Australia and Certain Seabed and Territorial Boundaries Between Indonesia and Papua New Guinea; Agreement between Indonesia and Australia concerning Certain Boundaries between Indonesia and Papua New Guinea; Memorandum of Understanding between The Government of The Republic of Indonesia and the Government of The Australia/Papua New Guinea concerning Administrative Border Arrangements; Agreement between the Government of Indonesia and the Government of Australia (Acting on Its own Behalf and on Behalf of the Government of Papua New Guinea) concerning Administrative Border Arrangements as to the Border between Papua New Guinea and Indonesia. This regulation is used as the basis for managing land borders between Indonesia and Papua New Guinea based on the opinion of Stephen B. Jones.